Network Governance of Rural Water Management to Cope with Adverse Impacts of Climate Change: Evidence from An Irrigated Dry Area in Central Java, Indonesia - Mohammad Rondhi; Syamsul Hadi; Muhamad Imanuddin; Yasuhiro Mori; Takumi Kondo; Rokhani Rokhani; Anik Suwandari; Ebban Bagus Kuntadi; Shohibul Ulum; Nita Anisya Firdaus (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Irrigation management in Indonesia has always involved challenges. There are at least three phases in irrigation management: the rain-fed phase, technical irrigation in irrigation buildings, and technical irrigation to mitigate climate change (CC). This study investigated irrigation management based on local wisdom as a form of CC adaptation. The research was conducted in Klambu Kanan Irrigation District (KKID), where 11,005 ha of rice fields are irrigated in three regencies. The subjects of this research were 40 irrigation Water User Associations (WUAs), and the research instrument was a model that provided incentives to manage WUAs, cropping patterns, and water fees in response to CC. The results showed that CC has had impacts on rice fields in the KKID, such as mud flooding due to changes in land cover. There are two models employed by the WUAs: a “self-governance model” (SGM) and an “auction model” (AM), the latter of which is a form of management based on “network governance” (NG). The SGM emphasizes the participation of members (community-based) through social capital, while the AM emphasizes the availability of capital in irrigation management (provider-based). More than 77% of WUAs employed the SGM, while the rest employed the AM. In addition, the SGM was utilized for 180 more days per year than the AM, which was used for 47 days per year. Finally, the productivity of the SGM was higher than that of AM. Further research is needed to compare SGM and AM to confirm that SGM is more widely applied than AM.